Evaluation of zero-dimensional furnace models for biomass-fired boilers with the aid of CFD and plant measurements - Kadakure, Tinashe (Department of Mechanical Engineering, 2025)
Biomass combustion is an important and renewable source of energy, and its efficient utilisation has become an area of active research. Modelling biomass boilers is critical for optimising their design, performance, and control. A key challenge is accurately predicting waterwall heat uptake, furnace exit gas temperature (FEGT), and direct radiation impinging on downstream heat exchangers under varying operational conditions. Although radiation heat transfer is highly dependent on three-dimensional geometry, one-dimensional process models that integrate zero-dimensional (0-D) furnace models are commonly used to predict boiler performance. 0-D models simplify complex systems by representing the furnace as a single control volume with averaged properties, rather than capturing spatial variations. These 0-D furnace models are typically based on a combination of fundamental and empirical relationships. However, it has been shown that the existing empirical relationships may not always capture the furnace performance with sufficient accuracy. This study evaluates the predictive accuracy of two widely used 0-D semi-empirical furnace models, the direct method (Hottel) and the projected method (Gurvich/Blokh). These 0-D models were originally developed for large coal-fired boilers, and they are often applied to biomass-fired boilers without a thorough evaluation of their performance. To address this gap, two case studies were conducted on a compact biomass-fired boiler and an industrial biomass-fired boiler, with steam flows of 45 t/h and 105 t/h, respectively. The accuracy of the 0-D furnace models was evaluated by comparing their predictions to validated CFD simulations at both full and reduced loads. Key performance indicators, including waterwall heat uptake and FEGT, were analysed to evaluate the predictive accuracy of the 0-D models. For the smaller boiler, the 0-D models exhibited limitations in accurately predicting radiation heat transfer, especially at reduced loads. Although the projected method outperformed the direct method in some cases, neither model accurately captured the performance of the smaller boiler. In contrast, for the larger boiler, the direct method predicted waterwall heat uptake within 5.1% of the CFD results at full and reduced loads. The projected method, while exhibiting limitations in predicting waterwall heat uptake, performed better in predicting the FEGT, with errors of less than 5.4% across all load conditions. This study highlights the limitations of 0-D furnace models when applied to biomass-fired boilers, particularly for smaller boilers and under reduced load conditions. This emphasises the need to refine these models for broader applicability beyond large coal-fired boilers.